2018
DOI: 10.1186/s13059-018-1588-9
|View full text |Cite
|
Sign up to set email alerts
|

miRTrace reveals the organismal origins of microRNA sequencing data

Abstract: We present here miRTrace, the first algorithm to trace microRNA sequencing data back to their taxonomic origins. This is a challenge with profound implications for forensics, parasitology, food control, and research settings where cross-contamination can compromise results. miRTrace accurately (> 99%) assigns real and simulated data to 14 important animal and plant groups, sensitively detects parasitic infection in mammals, and discovers the primate origin of single cells. Applying our algorithm to over 700 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…These disparities have obstructed comparative genomic approaches in the miRNA field: for example, missing miRNA families have been misinterpreted as secondary losses, questioning then the fundamental conservation of miRNA families(70). However, very similar miRNA complements in terms of total miRNA genes and miRNA families are observed in closely related groups in MirGeneDB(Figure 3), supporting earlier evolutionary studies arguing for the utility of miRNAs as excellent phylogenetic markers(11,37,53,68) (Figure 1).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…These disparities have obstructed comparative genomic approaches in the miRNA field: for example, missing miRNA families have been misinterpreted as secondary losses, questioning then the fundamental conservation of miRNA families(70). However, very similar miRNA complements in terms of total miRNA genes and miRNA families are observed in closely related groups in MirGeneDB(Figure 3), supporting earlier evolutionary studies arguing for the utility of miRNAs as excellent phylogenetic markers(11,37,53,68) (Figure 1).…”
mentioning
confidence: 52%
“…For the expansion from version 1.0 to 2.0, we analyzed more than 400 publicly available smallRNA sequencing datasets with at least one representative dataset for each organism, that were automatically downloaded and processed using sRNAbench (52) and miRTrace (53), respectively. This allowed for a consistent and uniform annotation of miRNAomes for each species using MirMiner (11) (see Supplementary Table, "file_info" for files and see…”
Section: Expansion Of Mirgenedbmentioning
confidence: 99%
“…Briefly, Illumina samples from ancient and historic (Smith et al 2019) as well as fresh tissues (Koenig et al 2016;Penso-Dolfin et al 2016) were downloaded from SRA using sra-toolkit 2.9.2 (Leinonen et al 2010), processed using miRTrace (Kang et al 2018) and quantified using the 'quantify' function of miRDeep2 (Friedländer et al 2012) with the MirGeneDB 2.0 dog microRNA complement as reference (Fromm et al 2019). Sequence comparisons to human and other vertebrate microRNA complements are based on MirGeneDB 2.0 annotations (Fromm et al 2019) and the consistent nomenclature of microRNA gene orthologues, paralogues and families (Fromm et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…They are the most conserved elements in metazoan genomes and have great potential as phylogenetic markers (Sempere et al 2006;Tarver et al 2013). We have recently curated the microRNA complements of 45 Metazoan organisms, including canid, in the MirGeneDB database (Fromm et al 2019) and shown that species-specific microRNAs can be used to trace the taxonomic origin of samples using our straightforward software miRTrace (Kang et al 2018). We here leverage these two resources to characterize the microRNA complements of the ancient and historic canid samples.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, new miRNAs are constantly evolving, and they have been proposed as phylogenetic markers [23] . Taking advantage of this idea, miRTrace was developed to predict the taxonomic diversity in any sRNA-Seq sample or detect the origin of cross-species contaminations [24] . Yet because it relies on a database of clade-specific miRNAs, it cannot classify sequences that have not been curated.…”
Section: Introductionmentioning
confidence: 99%